TAâLIK TALAK DALAM PERSPEKTIF FIQH DAN KOMPILASI HUKUM ISLAM (Analisis Perbandingan) - Sesse, Muh. Sudirman (DIKTUM: Jurnal Syariah dan Hukum, 2012)
This paper describes the problem Talik Separations Fiqhi perspective and Compilation of Islamic Law. Discussion of the results obtained by the understanding that: the problem Talik Separations, deviation occurs among the jurists, some of which allow and disallow others. While in Indonesia Talik Separations has existed since the Dutch era, and has undergone many changes even at the time of independence to the present, the formula had been established by the Ministry of Religious Affairs in order to protect his wife from ill-treatment from her husband. In the administrative procedures for the settlement of marriage Indonesia, proof of being part Talik Divorces are very important in order to meet the demands of applicable legislation for citizens, especially Muslims, this is important because it is one evidence in court, in case of contested divorce.